STRUCTURE ANALYSIS AND MANUFACTURING OF WINGS TRAINER-5774 - Suciari Dewi Triani; Moh Ardi Cahyono; Lazuardy Rahendra Pinandhita (Institut Teknologi Dirgantara Adisutjipto, 2020)
Unmanned Aerial Vechicle (UAV) is one of the types an aircraft. Trainer is part of an airplane where the aircraft is controlled by a remote control for its flight. One of the things that must be considred in design an airplane is strength and and resistance of the wing structure in accepting distributed aircraft loads. In addition to the structural design and load, the material to be used can have an effect. The process is starting from modification of the aircraft wing using CATIA V5R20 which is then carried out analysis of the wing structure by being given the aircraft load using ANSYS 19. The largest structural value is in the Joiner section of 7,967 with manuvering load and smallest value is 0,026 on the Spar section. Margin of safety smallest value in the spar when its manuver. After analysis it is continued with the manufacturing process according to the design that has been made.